Capacity development exercises interoperability side with private competition and the impact of the correction accurately and falling pitch (7) M in Handball - Shinen, Abdul Jabar (Journal of Physical Education, 2011)
الخلاصة | الكلمات الدلالية | النص الكامل | تصدير | الاصداراتالخلاصةresearcher. A.p. Abdul-Jabbar al-Janabi, the University of Kufa Girls College of Education / Department of Physical Education Highlights the importance of being able harmonic movements vehicle that require moving more than one member of the body at the time of one, and getting those important if the movement of the body in different directions for the outcome of force in a certain direction, as happens in the movement of types of correction in the handball that need to be various movements and straight to get the best position of the motor correction . The research aims to - To identify the impact of exercise on the development of private competition capacity interoperability among a sample experimental research - To identify the impact of the development capacity on the accuracy of harmonic correction of an imam and falling pitch (7) m in handball in a sample experimental research . - To identify the significant differences in the post tests between the sample and experimental Aaldhabtp . The researcher used the experimental approach using experimental design for the two groups, experimental and control group practice pre and post test for relevance to the nature of this study. Determine the way the research community by students deliberate phase III in the Department of Physical Education / Faculty of Education for Girls / University of Kufa for the academic year (2009-2010) and of their number (47) students. Selected sample of the research method of simple random from the original research community, and the number (36) students, were divided equally into two groups randomly and in a manner of lots to determine the two groups (experimental and control groups) . The research came to the following : Training curriculum used by the researcher has a clear positive impact on the development of some capacity interoperability (compatibility hands with the eye, the two men agree with the eye, the compatibility of the total body of experimental research sample . Harmonic development of the ability to sample experimental research, has had a positive impact on the development of precision as an imam and throws (7m). Than the experimental group to control group in the post tests for interoperability tests the ability and accuracy of pitch correction and an imam (7 m). The researcher recommended the following : Altoavqp emphasize the development of capacity in all lessons and all the stages and skills through learning and development in all of the games of individual and collective, that the skills acquired and developed through to refine and improve the muscle groups involved in the performance . Develop a program to develop motor skills, including the compatibility of all games. And knowledge of their adequacy for the development of motor skills for each game. Development of motor skills tests as part of the final exams for the school year to detect the seriousness of the student and follow-up of a desire to develop their levels during the practical lessons during the school yearء